Enhancing nutritional yields through efficient crop diversification: comparison to the common of rice-rice system in Bangladesh. Comparing diversified cropping patterns in Dinajpur, Bangladesh - Washiq, Faisal; Krupnik, Timothy J.; Hossain, Akbar; Aonti, Annika Jahan; Md. Mobinur Rahman; Gathala, Mahesh Kumar (2024)
Focusing on economic access to nutritious foods, updated and improved estimates show that more than one-third of people in the world – about 2.8 billion – could not afford a healthy diet in 2022. low-income countries having the largest percentage of the population that is unable to afford a healthy diet (71.5 percent). (FAO, 2024) This research note focuses to accelerate the transformation of our agrifood systems through introducing different diversified cropping options especially for the northern part of Bangladesh to strengthen their resilience to the major drivers and address inequalities to ensure that healthy diets are affordable and available to all. The research trial was established at the Bangladesh Wheat and Maize Research Institute (BWMRI) in Dinajpur, Bangladesh in August 2022.